Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content 1. The Awareness level of Students of the Education College in the State of Kuwait about the Digital Citizenship Dimensions Mr. Abdulaziz Mutlaq Saad Al-Watari Al-Rashidi, Dr. Farah Abdulaziz Al-Mutawa 2. The Extent of Awareness to Which the Academic Body and Students at the University of Nizwa Understand the Concept of Governance (Traditional and Electronic) Ms. Huda Mohammed Juma Attia, Dr. Radhia Sulaiman Nasser Al-Habsi 3. Reality of female Islamic studies teachers promoting values of volunteer work among female secondary school students in Makkah Prof. Hoba Ahmed Akram, Ms. Reem Mohammed Almontashri 4. Transformational Leadership Among Government School Principals and Its Relationship to Teachers’ Professional Compatibility in The Governorate of South Al-Sharqiyah in The Sultanate of Oman Mr. Tariq Juma Al-Rasbi, Dr. Rabia Al-Mur Al-Dhuhli, Dr. Radhiya Sulaiman Al-Habsi, Dr. Yaqoob Salim Al-Thani 5. The reality of the contributions of associations of people with disabilities in achieving their social empowerment An applied study on care centers for persons with disabilities in the city of Hail Ms. Jawaher Ghazi Al-Ashqar 6. Challenges of Implementing E-Learning in Upper Elementary Education: Perspectives of Abu Al-‘Arqan School Teachers, South Hebron Ms. Hiyam Yousssef Daraweesh, Dr. Ibrahim Mohammad Arman